2015
DOI: 10.1016/j.foodpol.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of ethanol policy on corn prices: A review and meta-analysis of recent evidence

Abstract: The literature on the impacts of biofuels on food prices is characterized by contradictory findings and a wide range of estimates. To bring more clarity to this issue, we review studies on U.S. corn ethanol expansion released between 2008 and 2013. Normalizing corn price impacts by the increase in corn ethanol volume, we find that each billion gallon expansion in ethanol production yields a 2-3 percent increase in corn prices on average across studies. We also conduct a meta-analysis to identify the factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 54 publications
(45 reference statements)
2
54
1
1
Order By: Relevance
“…These mandate relaxations under the ample supply case (the 2015 yield projection) have the same effect for any mandate at 49.21 billion liters or less. On the other hand, when a 2012-like production shortfall occurs, the larger the relaxation, the less the increase in corn price (as also found in Condon et al [8]). Interestingly, our model also showed that, when mandates were removed, corn ethanol production was reduced to levels between 15.52 billion liters under the shortfall and 18.55 under normal yields.…”
Section: Rfs2 and Corn Ethanolmentioning
confidence: 56%
See 2 more Smart Citations
“…These mandate relaxations under the ample supply case (the 2015 yield projection) have the same effect for any mandate at 49.21 billion liters or less. On the other hand, when a 2012-like production shortfall occurs, the larger the relaxation, the less the increase in corn price (as also found in Condon et al [8]). Interestingly, our model also showed that, when mandates were removed, corn ethanol production was reduced to levels between 15.52 billion liters under the shortfall and 18.55 under normal yields.…”
Section: Rfs2 and Corn Ethanolmentioning
confidence: 56%
“…In this review, we will focus on studies that analyze policies after the introduction of RFS2. Many studies have concluded that the ethanol mandate increased commodity prices [7][8][9]. Condon et al [8] conducted a meta-analysis and indicated that each additional 3.79 billion-liter (1 billion gallon) expansion in the corn ethanol mandate would lead to a three to four percent increase in 2015 corn prices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Al respecto Condon et al (2015) determinaron que un aumento en la demanda de un millón de galones de etanol, se reeja en un incremento del precio del maíz entre un 3 y 4 %.…”
Section: Resultados Y Discusiónunclassified
“…Biofuel mandates that had recently been introduced in the US and the EU contributed to the increase in crop and food prices (see the National Research Council 2011, Roberts and Schlenker 2013, Chen and Khanna 2013, and Condon et al 2015, and in the US, there was a sharp increase in the use of corn as the feedstock for ethanol production. The policy has transformed US corn production, impacted world food supply, and reshaped agricultural land use within and outside of the US (Khanna andCrago 2013 andNuñez et al 2013), despite a subsequent restriction on the share of corn ethanol in total biofuels quota in 2007.…”
Section: Introductionmentioning
confidence: 99%